Reduced grazing and changes in the area of agroforestry in Europe - Rubio-Delgado, Judit; Schnabel, Susanne; Burgess, Paul J.; Burbi, Sara (Frontiers in Environmental Science, 2023)
Agroforestry integrates woody vegetation with crop and/or livestock production to benefit from the ecological and economic interactions. The objective of this paper is to systematically determine the spatial distribution of agroforestry in the EU, and changes in the areas and types of agroforestry from 2009 to 2018. This was achieved using the Land Use/Cover Area Statistical (LUCAS) dataset. Agroforestry was categorised into silvopastoral, silvoarable, agrosilvopastoral, grazed permanent crops, intercropped permanent crops and kitchen gardens systems. In our categorisation of 'agroforestry', sites combing trees and shrubs with understorey grass or forage were required to show evidence of grazing. In 2018, the total area of agroforestry in the EU28 was 114,621 km 2 equivalent to 6.4% of the utilised agricultural area (UAA), and a majority located in the Mediterranean bioregion. Silvopastoral was the most widespread system, representing 81% of the total agroforestry area (5% of UAA), with almost a third of that area present in Spain. An initial analysis of the LUCAS data suggested that the area of agroforestry increased from 2009 to 2012, before declining from 2012 to 2018. However our subsequent analysis suggests that the area of agroforestry in 2009 was underestimated due to a mis-categorisation of some grazing areas. After making corrections, we calculated that the area of agroforestry (using the above definitions) in the EU23 (a fulltime sequence for the EU28 is unavailable) declined by 47% between 2009 and 2018. This decline is primarily due to a reduction in outdoor grazing, perhaps driven by reduced livestock numbers and/or permanent livestock housing. The only agroforestry system showing an increase was kitchen gardens (7%). The paper highlights the usefulness of the LUCAS dataset for studying the extent of agroforestry in Europe, but also potential limitations in terms of the consistency of the location of data points and the categorisation of grazing. The paper also argues that although the area of withinfield agroforestry may be declining, the drive towards net zero greenhouse gas emissions may be re-establishing the link between increased tree cover and food production at a farm-level.